Electrochemical Conversion of CO2 into Valuable Carbon Nanotubes: The Insights into Metallic Electrodes Screening. Issue 4 (11th February 2020) - Li, Zhida; Zhang, Wenyong; Ji, Deqiang; Liu, Shihao; Cheng, Yuan; Han, Jiaqi; Wu, Hongjun
Abstract : Direct conversion of CO2 to reusable solid carbon products based on the molten salts electrochemistry demonstrates a feasible approach to address the intractable global climate change. In this work, we compare a series of conventional metal electrodes and figure out why Fe cathode and Ni anode are superior to other metallic electrodes for molten carbonates electrolysis by polarization measurements, which could be utilized as a universal methodology for electrode candidates screening. The cyclic voltammetry measurements help to gain a richer understanding on the CO3 2− reduction and carbon formation process on metal electrodes. Moreover, to elucidate the formation mechanism of carbon nanotubes on Fe cathode, low-current electrolysis was conducted and Ni nanoparticles were observed to disperse on the cathode surface evenly. All of the obtained information provides a reasonable explanation to why carbon deposition occurs and how carbon nanotubes form, which should be of great interest for the following industrial carbon nanotubes production based on the molten salts manner.